2018
DOI: 10.1016/j.jid.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Mediates IgA Autoreactivity in Drug-Induced Linear IgA Bullous Dermatosis

Abstract: Vancomycin (VCM) is known to induce linear IgA bullous dermatosis (LAD). However, in contrast to conventional LAD, in which circulating IgA autoantibodies against basement membrane proteins are commonly detected, patient sera from VCM-induced LAD yields negative results in indirect immunofluorescence microscopy, and the targeted autoantigen remains undetermined. By using sera from a typical patient with VCM-induced LAD, we identified that co-incubation of sera with VCM resulted in linear IgA deposition at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
(39 reference statements)
0
25
0
7
Order By: Relevance
“…Yamagami et al . recently demonstrated that the NC1 domain of VII collagen could be a target antigen in VCM‐induced DILAD .…”
Section: Discussionmentioning
confidence: 99%
“…Yamagami et al . recently demonstrated that the NC1 domain of VII collagen could be a target antigen in VCM‐induced DILAD .…”
Section: Discussionmentioning
confidence: 99%
“…Diese ist eine autoimmun bedingte Hauterkrankung, die durch die Ausbildung subepidermaler Blasen gekennzeichnet ist. Sie kann entweder idiopathisch oder medikamenteninduziert auftreten, wobei Vancomycin häufigster medikamentöser Auslöser ist [12]. Das klinische Bild, sowohl der idiopathischen als auch der medikamenteninduzierten Form, ist variabel und kann andere blasenbildende Erkrankungen nachahmen.…”
Section: Diskussionunclassified
“…Die lineare IgA-Dermatose ist deutlich seltener. Die Häufigkeit dieser Erkrankung wird in verschiedenen Ländern zwischen weniger als 0,5 und 2,3 Fällen pro Million Einwohner pro Jahr angegeben [12]. Eine umfangreiche Untersuchung aus dem Iran über autoimmunbedingte blasenbildende Dermatosen über einen Zeitraum von 10 Jahren beschreibt das Auftreten der linearen IgA-Dermatose bei nur 0,3 % des beobachteten Patientenkollektivs [3].…”
Section: Diskussionunclassified
See 2 more Smart Citations